Diagnosis of Proximal Dental Caries Using Intraoral and Extraoral Bitewing Radiographs: A Narrative Review - Indira Aqlyya Oktavian; Rini Widyaningrum; Rellyca Sola Gracea (Indonesian Dental Association, 2023)
Radiographic examination using intraoral bitewing (IOBW) radiography is an ideal examination to detect proximal carious lesions. Besides the risk of triggering gag reflex, the IOBW technique is susceptible to SARS-CoV-2 virus transmission through saliva-contaminated film or digital sensor. Examination using intraoral techniques during the COVID-19 pandemic should be avoided to minimize cross-contamination of the SARS-CoV-2 virus. The alteration from using IOBW to extraoral bitewing (EOBW) radiography can be a promising alternative to overcome these problems. This review article aims to describe the advantages of the EOBW technique and compares diagnostic performance of IOBW and EOBW radiographs in detecting proximal dental caries. The databases used for literature searching in the review include Google Scholar, PubMed, and Science Direct. The inclusion criteria were original articles, case reports, and English and Indonesian scientific textbooks published from 2010 to 2021. The exclusion criteria were article reviews and original articles that did not contain research methods. A total of 29 literatures were discussed in this narrative review. The EOBW technique is recommended during the COVID-19 pandemic to reduce the risk of cross-contamination in dental radiography. This technique ensures the patient for a more comfortable procedure, with shorter time needed and a wider field of view that allows it to be used to detect bone loss in the alveolar crest. Sensitivity, specificity, and area-under-curve in the IOBW technique were higher than in the EOBW. Nevertheless, EOBW shows good accuracy, so it can be used as an alternative technique for patients who find it difficult to undergo the IOBW technique, especially during the COVID-19 pandemic.